Listeria monocytogenes environmental sampling program in ready‐to‐eat processing facilities: A practical approach. Issue 6 (20th August 2020) - Spanu, Carlo; Jordan, Kieran
Abstract: Listeria monocytogenes is a foodborne pathogen that is frequently found in the environment. It can easily enter food processing environments and contaminate food, potentially causing public health issues. Food business operators (FBOs) are responsible for the control of L. monocytogenes in the food processing environment, particularly in facilities producing ready‐to‐eat food. The design and implementation of an effective environmental monitoring program (EMP) for L. monocytogenes is an integral part of controlling L. monocytogenes . An effective EMP, including all aspects from sampling, to analysis, to data interpretation, to implementation of corrective actions (including food disposition), is a tool that will help with identification and control of L. monocytogenes contamination. It should be used in conjunction with end product testing, not as a replacement for it. An EMP should be specifically designed for a particular facility on a case‐by‐case risk‐based approach, by a food safety team within the facility. It should be reviewed regularly (at least every 6 months) and verified for its effectiveness. The control of L. monocytogenes in the food industry involves the full commitment of management and of all personnel involved with the safety of foods placed on the market, thus reducing the risk of listeriosis to consumers. Several regulatory and guidance documents provide recommendations for designing aspects of an effective L. monocytogenes EMP. However, a comprehensive review of the key components of an EMP in a single document is lacking. The objective of the present review is to provide FBOs with a practical guide to design, implementation, and verification of an EMP tailored by the food safety team for each food business.